Violence Against Children - Jace Pillay (The Thinker)
Violence against children (VAC) is a global phenomenon that needs deliberate attention. Children exposed to violence in their families, communities, and schools in their early years are likely to maintain this cycle of violence in their youth and adult lives if no efforts are made to break this cycle. Taking this into consideration the author adopts a social-ecological theoretical perspective in exploring global, regional, and South African literature on the risks and causes of VAC as well as the protective factors that can prevent VAC. Embedding VAC within a social-ecological perspective warrants the need to explore it at four crucial levels, namely individual, relationships, community, and society. The literature review embodies the relevance of these four levels since all risk and causal factors of VAC are easily categorised in one or more of these levels. As such, the author provides a social-ecological perspective comprising all four levels that holistically address the prevention of VAC. The literature review indicated that many of the risks and causes of VAC are a common trend across countries even though it is more prevalent within African contexts. This suggests that the preventive measures discussed are likely to have global value.